2021
DOI: 10.1101/2021.07.01.450507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behaviourally modulated hippocampal theta oscillations in the ferret persist during both locomotion and immobility

Abstract: Theta oscillations are a hallmark of hippocampal activity across mammalian species and play a critical role in many hippocampal models of memory and spatial navigation. To attempt to reconcile the cross-species differences observed in the presence and properties of theta, we recorded hippocampal local field potentials in rats and ferrets during a localisation task designed to vary locomotion and sensory attention. Here we show that theta oscillations occur during locomotion in both the ferret and rat, however … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…Despite the importance of these areas and the parallels in auditory and visual scene analysis, there is (to our knowledge) little known about the role of structures such as the hippocampus in spatial hearing. Recordings from echo-locating bats indicates that hippocampal function and auditory processing may be closely linked (Ulanovsky and Moss, 2007;Wohlgemuth et al, 2018), and in ferrets, hippocampal theta oscillations are widespread during approach-to-target sound localization (Dunn et al, 2021). Determining how the auditory system interacts with the medial temporal network, as well as parietal cortex, may thus provide important new insights into coordinate frame transformations in spatial hearing, and scene analysis more generally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the importance of these areas and the parallels in auditory and visual scene analysis, there is (to our knowledge) little known about the role of structures such as the hippocampus in spatial hearing. Recordings from echo-locating bats indicates that hippocampal function and auditory processing may be closely linked (Ulanovsky and Moss, 2007;Wohlgemuth et al, 2018), and in ferrets, hippocampal theta oscillations are widespread during approach-to-target sound localization (Dunn et al, 2021). Determining how the auditory system interacts with the medial temporal network, as well as parietal cortex, may thus provide important new insights into coordinate frame transformations in spatial hearing, and scene analysis more generally.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to sound presentation, the subject was required to hold at the port for a variable delay (from 0.2 to 0.7 s), and trials would only be successfully initiated if the animal remained in position through the full duration of the sound. This hold period ensured that animals had a stationary head position during sound presentation (Dunn et al, 2021) and thus minimized any available dynamic localization cues. To encourage subjects to hold at the center port, rewards were delivered at this location on randomly allocated trials with a variable probability (up to 10% of trials).…”
Section: Task Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to sound presentation, the subject was required to hold at the port for a variable delay (from 0.2 to 0.7 s), and trials would only be successfully initiated if the animal remained in position through the full duration of the sound. This hold period ensured that animals had a stationary head position during sound presentation (Dunn et al, 2021) and thus minimized any available dynamic localization cues. To encourage subjects to hold at the center port, rewards were delivered at this location on randomly allocated trials with a variable probability (upto 10% of trials).…”
Section: Methodsmentioning
confidence: 99%
“…In animals, administration of cholinergic antagonists disrupts the generation and tuning of hippocampal theta oscillations (Kramis et al, 1975;Teitelbaum et al, 1975;Monmaur et al, 1997;Asaka et al, 2000) whereas cholinergic agonists induce theta activity (Konopacki et al, 1987;Huerta and Lisman, 1993). Specifically, in rodents, cholinergic blockade inhibits immobility-related slow theta oscillations (4-7 Hz) but spares movement-related fast theta (7)(8)(9)(10)(11)(12), revealing a distinction between cholinergic-sensitive slow theta ("Type 2") and cholinergic-resistant fast theta ("Type 1") (Kramis et al, 1975;Dunn et al, 2021). This link between cholinergic modulation and theta oscillations is important because extensive research has shown that hippocampal theta oscillations contribute critically to memory processing (Buzsáki, 2002;Burgess et al, 2002;Colgin, 2013;Orr et al, 2001), specifically by coordinating spike timing (O'Keefe and Recce, 1993;Lisman and Idiart, 1995;Rutishauser et al, 2010).…”
Section: Introductionmentioning
confidence: 99%